Podcast Project: Anti-corruption Education to Improve Human Resources in the VUCA Era (Universitas Terbuka, 2023)
As one of the most corrupt countries in Southeast Asia, Indonesia needs to take preventive steps. One of them is by providing anti-corruption education to the younger generation. Anti-corruption education is needed to improve human resources in the current VUCA era. Anti-corruption education is given to students because youth are the future of the country and nation. One function of the basic sociological concept is the medium of communication. As Löw said, distant spaces and different spaces can be combined through the verbal and visual contact provided by telecommunications technology. Now we live together with gadgets and digital media, one of which the public is interested in is podcasts. Podcasts are not limited by space and time, so they can be accessed by the public. The podcast project was created so that students, who are the younger generation, are aware of issues of corruption in everyday life. This study aims to analyze podcasts as an anti-corruption educational medium for youth. This study uses qualitative analysis with a case study approach. The results of the study show that anti-corruption education through podcasts is of interest to the younger generation. The podcast project as an anti-corruption education medium is one of the right preventive steps to improve the quality of human resources. Podcast projects carried out by youth can be disseminated to the public to increase public awareness regarding corruption.